<h3>
Answer: reflection over x axis</h3>
g(x) = -f(x) is the same as g(x) = -1*f(x)
Since y = f(x), we are really saying g(x) = -1*y. Whatever the y coordinate is on f(x), multiply it by -1. This turns something like y = 2 into y = -2, or something like y = -3 into y = 3, etc etc. Visually this reflects the point over the horizontal x axis. Do this to all points on f(x), and the entire curve reflects over the x axis.
I show an example of y = x^2 turn into y = -x^2 in the attached image below.
Answer:
A. -41/15.
Step-by-step explanation:
15x^2 + 23x - 41 = 0
Product of the roots of ax^2 + bx + c = c/a.
Thus the product of the roots of this equation = -41/15.
<span>lIt occurs in the left parietal lobe.
Happy studying ^-^</span>
Answer:
B
Just multiply by 4 to isolate x; because 4 isn't negative, u keep the sign the same.